GROWTH RESPONSE OF BEHA GRASS (Brachiaria humidicola) FERTILIZED WITH GOAT MANURE - Budiman, Budiman; Sandiah, Natsir; Malesi, La (Pascasarjana Universitas Sulawesi Tenggara, 2020)
This study aimed to determine the best dosage of goat manure as a natural fertilizer on Beha grass(Brachiaria humidicola). This study used 64 poles of Beha grass grown in polybags divided into 16plots, and it used a completely randomized design (CRD) to analyze the data. This study consist of 4treatments that is P0 (0 ton/ha of goat manure), P1 (10 ton/ha of goat manure), P2 (15 ton/ha of goatmanure), and P3 (20 ton/ha of goat manure). This study's variables were plant height, number of leaves,numbers of tillers, new production, and root length. Data analysis used ANOVA variance continued withreal honest difference test. The result of this study showed that averages of plant height (cm) wereP0=26, P1=50.5, P2=51.5, and P3=52.75. Averages of the number of leaves were P0=22, P1=110,P2=160, and P3=185. Averages of numbers of tillers were P0=7, P1=25, P2=37, and P3=38. Averages ofnew production (g) were P0=17.75, P1=123.5, P2=178, and P3=192.25. Averages of root length (cm)were P0=37.8, P1=39.5, P2=41.775, and P3=49.5. Fertilization with natural fertilizer from goat manurehas a genuine effect (P<0.01) on the growth of Beha grass. The best dosage of fertilization with goatmanure was 15 ton/ha.